2008
DOI: 10.1103/physrevc.78.024301
|View full text |Cite
|
Sign up to set email alerts
|

AnalogE1transitions and isospin mixing

Abstract: We investigate whether isospin mixing can be determined in a model-independent way from the relative strength of E1 transitions in mirror nuclei. The specific examples considered are the A = 31 and A = 35 mirror pairs, where a serious discrepancy between the strengths of 7/2 − → 5/2 + transitions in the respective mirror nuclei has been observed. A theoretical analysis of the problem suggests that it ought to be possible to disentangle the isospin mixing in the initial and final states given sufficient informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…3), which suggests a similar structure of the 1/2 + state in the mirror pair and supports the hypothesis that the observed change in the E 1 decay pattern probes the degree of mixing between the two 3/2 − states. The amount of isospin mixing needed to explain the E 1 asymmetry for a low-lying 7/2 − level in the A = 35 and a 9/2 + stateintheA = 67 mirror nuclei was estimated to be on the order of 1-5% [4,[7][8][9]. In contrast to Refs.…”
Section: Co Nimentioning
confidence: 61%
See 2 more Smart Citations
“…3), which suggests a similar structure of the 1/2 + state in the mirror pair and supports the hypothesis that the observed change in the E 1 decay pattern probes the degree of mixing between the two 3/2 − states. The amount of isospin mixing needed to explain the E 1 asymmetry for a low-lying 7/2 − level in the A = 35 and a 9/2 + stateintheA = 67 mirror nuclei was estimated to be on the order of 1-5% [4,[7][8][9]. In contrast to Refs.…”
Section: Co Nimentioning
confidence: 61%
“…In both cases the first E 1matrix element is also comparably large. We note that an E 1 transition between pure (2s 1/2 ) −1 (1 f 7/2 ) 8 hole and (1 f 7/2 ) 6 (2p 3/2 ) 1 particle configurations for the 1/2 + and 3/2 − , respectively, would be forbidden. Consequently, more complex configurations have to be present to explain the enhanced E 1 rates.…”
Section: Co Nimentioning
confidence: 81%
See 1 more Smart Citation
“…Despite the fact that isospin rules dictate that the B(E1) should be identical in mirror nuclei, some cases of strong asymmetries in B(E1) strengths have been indicated by recent data, especially in the A = 35 [34] and A = 31 [35] mirror pairs, and the factor of 40 here does not seem out of line. A summary of the current situation regarding these asymmetries is given by Pattabiraman et al [36] where factors ranging from 40 to 50 were also presented. For the nuclei presented in that work, the E1 transitions were weak (10 −6 or 10 −7 Wu) and the analysis showed that, at least in the case of A = 35, such weak transition strengths can be strongly perturbed in the presence of moderate isospin-mixing at the level of 1%, causing an asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…A beam of 36 Ar was accelerated to 95 MeV by the AT-LAS facility at Argonne National Laboratory. The beam nuclei impinged on a 0.25 mg/cm 2 10 B target to produce 46 V as a compound nucleus.…”
Section: Experimental Techniquementioning
confidence: 99%